2016
DOI: 10.1002/joc.4737
|View full text |Cite
|
Sign up to set email alerts
|

Regional characteristics of long‐term changes in total and extreme precipitations over China and their links to atmospheric–oceanic features

Abstract: ABSTRACT:The regional features of long-term changes in total and extreme precipitations over eight China domains and their seasonality and relationships with large-scale and local atmospheric and oceanic factors are investigated. A newly compiled data set of 917 China stations from the China National Meteorological Information Center with strict quality control is analysed. Wintertime extreme precipitation has increased persistently in all China domains, together with an obvious wetting tendency except in Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 76 publications
(103 reference statements)
1
23
0
Order By: Relevance
“…2). This also agrees with the results of [36], who found that while the intensity of summer precipitation in Sonora state increased significantly since 1977, in association with the +PDO phase, the monsoon season became shorter, resulting in a non-significant upward trend in precipitation [10] (Figs 2a-c). The linear trend of the percentage contribution of P95 associated with TCs was significantly increased (0.86% decade -1 , p<0.05) during the period 1961-2000 (Fig.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…2). This also agrees with the results of [36], who found that while the intensity of summer precipitation in Sonora state increased significantly since 1977, in association with the +PDO phase, the monsoon season became shorter, resulting in a non-significant upward trend in precipitation [10] (Figs 2a-c). The linear trend of the percentage contribution of P95 associated with TCs was significantly increased (0.86% decade -1 , p<0.05) during the period 1961-2000 (Fig.…”
supporting
confidence: 92%
“…[7][8][9]. Increases in positive anomalies of relative humidity, surface temperature, SST and negative anomalies of radiation are environmental phenomena that can take place in the NAM and can cause the highest precipitations in the CNAM [10][11][12][13], which is common during the summer and influenced by the NAM and events from TCs. Recently, it has been argued that one of the biggest impacts of climate change will result from increased AADEP with return periods that can happen at any time, anywhere on the planet [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observed 1961-2012 precipitation trends over China do not exceed 2 mm year −1 in any season in any region (Wang and Yang, 2017). The interannual variability of the EOT time series are typically 2 orders of magnitude larger.…”
Section: Metum Simulationsmentioning
confidence: 89%
“…Several studies reported that annual extreme precipitation has increased in northwest China (Zhang et al, 2012;Jiang et al, 2013), the middle and lower reaches of the Yangtze River basin, parts of the southwest and south China coastal areas (Zhai et al, 2005), and decreased in north China (Fan et al, 2012), Yellow River basin (Fu et al, 2013) and the Sichuan Basin (Zhai et al, 2005). Increasing trends of extreme precipitation have been observed in all seasons in northwest China, but in the Yangtze River basin, extreme precipitation only increased in winter and summer (Wang and Yang, 2017). Thus, seasonal features are important for gaining more detailed information of changes in extreme precipitation.…”
Section: Introductionmentioning
confidence: 99%